Domesday text translation - Various (The University of Hull)
An electronic transcription of the translation of Domesday Book for 33 counties (Yorkshire is omitted for copyright reasons) originally published by Phillimore (1975-86) and edited by John Morris and others. An electronic edition of the text for Great Domesday was published by Phillimore as Domesday Explorer in 2000, edited by John Palmer, Matthew Palmer and George Slater. The electronic text of Little Domesday is new to this edition. In the interest of greater consistency but following the principles laid down by John Morris, the text has been revised for this edition by Caroline and Frank Thorn. A new translation for Yorkshire is being prepared by Caroline and Frank Thorn.